2023
DOI: 10.1021/acs.jafc.2c08646
|View full text |Cite
|
Sign up to set email alerts
|

Modification of a Novel Umami Octapeptide with Trypsin Hydrolysis Sites via Homology Modeling and Molecular Docking

Abstract: Increasing the copy number of peptides is an effective method to genetically engineer recombinant expression and obtain umami peptides in large quantities. However, the umami taste value of multicopy number umami peptides is lower than the single ones, thus limiting the industrial application of recombinantly expressed umami peptides. With aims to solve this problem, modification of an umami beefy meaty peptide (BMP) with trypsin hydrolysis sites was carried out via homology modeling and molecular docking in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…There are 22 peptides with the greatest potential umami taste according to the machine learning prediction tools (BIOPEP-UWM, Umami_PREL, Umami_YYDS). The MolProbity Ramachandran plot (Figure S1) showed that the stereochemistry of the built receptor model residues was reasonable, with 93.7% in the favored area and 98.7% in the allowed area, similar to the results of Cheng et al [33]. From the docking results (Table S1), ten peptides with intensities larger than 5 × 10 6 and binding energies lower than −8.9 kcal/mol were selected for solid-phase synthesis and sensory evaluation.…”
Section: Virtual Screening Of Umami Peptidessupporting
confidence: 83%
“…There are 22 peptides with the greatest potential umami taste according to the machine learning prediction tools (BIOPEP-UWM, Umami_PREL, Umami_YYDS). The MolProbity Ramachandran plot (Figure S1) showed that the stereochemistry of the built receptor model residues was reasonable, with 93.7% in the favored area and 98.7% in the allowed area, similar to the results of Cheng et al [33]. From the docking results (Table S1), ten peptides with intensities larger than 5 × 10 6 and binding energies lower than −8.9 kcal/mol were selected for solid-phase synthesis and sensory evaluation.…”
Section: Virtual Screening Of Umami Peptidessupporting
confidence: 83%
“…The composition of Pixian Douban (PXDB), which includes lipids, polyphenols, and various other components ( Yang et al, 2021 ), presents a significant challenge for peptide identification in these samples. To address this challenge, MCX solid-phase columns were utilized to enrich peptides and reduce impurities, as previously described ( Cheng et al, 2023 ). Furthermore, FBMN employs advanced algorithms to swiftly filter and process large datasets obtained from multidimensional high-resolution mass spectrometry.…”
Section: Resultsmentioning
confidence: 99%
“…This affinity is influenced by the closed conformation of T1R1 ( Fig. S2 B), which results in a less accessible binding cavity ( Cheng et al, 2023 , Dang et al, 2019 , López Cascales et al, 2010 ).…”
Section: Resultsmentioning
confidence: 99%
“…4 The peptides with a higher proportion of E and D possess more umami intensity. 5 Sensory evaluation shows that a strong umami taste is found in umami peptides with the structures of EE, 6 EDE, 7 DEE, and DD. [8][9][10] Besides, more hydrophobic amino acid residues in peptides tend to give a bitter taste, and the peptides made of hydrophobic amino acid residues are more bitter than the mixtures of these free amino acids.…”
Section: Introductionmentioning
confidence: 99%